The Role Of Insulin Resistance In Hypertension-The Pathophysiological Mechanisms (The Review of Diabetic Studies, 2025)
Background/Objectives: Considering that insulin resistance has been identified as a potential cause of hypertension and that hypertension remains the primary cause of cardiologic disease, in this study, we aimed to summarize the pathophysiologic mechanisms linking insulin resistance and hypertension.Methods: A literature search was conducted in the electronic database “PubMed”. Studies from the last 15 years were identified. The primary selection was based on abstract contents, whereas the final selection was made after the full texts were read.Results: We found that insulin resistance contributes to hypertension through numerous mechanisms. Studies have linked compensatory hyperinsulinemia to hypertension through the activation of the sympathetic nervous system and abnormal activation of the renin–angiotensin–aldosterone system, leading to sodium retention. Furthermore, insulin resistance impedes the vasodilatory effect of insulin by blocking its ability to release nitric oxide. Hypertensive patients presented increased levels of asymmetric dimethylarginine, a nitric oxide inhibitor. Early stages of insulin resistance are associated with increased affinity and capacity of endothelin-1 receptors and increased secretion of endothelin-1, a potent vasoconstrictor. Obesity, endothelial dysfunction, insulin resistance in cardiomyocytes and activation of mineralocorticoid receptors are also linked to both insulin resistance and hypertension. Conclusions: Available evidence suggests that insulin resistance plays an important role in the pathophysiology of hypertension. Its contribution to the development and progression of hypertension should not be overlooked. More studies are needed to elucidate the molecular and cellular mechanisms involved and develop an effective strategy for the prevention and treatment of hypertension in insulin-resistant patients.